2017
DOI: 10.12688/f1000research.11034.1
|View full text |Cite
|
Sign up to set email alerts
|

Wnt target genes and where to find them

Abstract: Wnt/β-catenin signaling is highly conserved throughout metazoans, is required for numerous essential events in development, and serves as a stem cell niche signal in many contexts. Misregulation of the pathway is linked to several human pathologies, most notably cancer. Wnt stimulation results in stabilization and nuclear import of β-catenin, which then acts as a transcriptional co-activator. Transcription factors of the T-cell family (TCF) are the best-characterized nuclear binding partners of β-catenin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 110 publications
(142 reference statements)
5
63
0
1
Order By: Relevance
“…While invertebrates contain one TCF, which participates in both sides of the transcriptional switch (Figure B), the presence of multiple TCFs in vertebrates has long raised the question of whether they have specialized transcriptional functions. Many genetic studies support the view that TCF3 (also known as TCF7L1) is a dedicated repressor and LEF1 a dedicated activator of Wnt targets, while TCF1 and TCF4 (also termed TCF7 and TCF7L2, respectively) display either activity depending on the context . Partially supporting this, TCF3 and TCF4 bind to TLEs with higher affinity than LEF1 or TCF1 .…”
Section: Is Tcf3 a Dedicated Repressor In The Transcriptional Switch?mentioning
confidence: 95%
See 1 more Smart Citation
“…While invertebrates contain one TCF, which participates in both sides of the transcriptional switch (Figure B), the presence of multiple TCFs in vertebrates has long raised the question of whether they have specialized transcriptional functions. Many genetic studies support the view that TCF3 (also known as TCF7L1) is a dedicated repressor and LEF1 a dedicated activator of Wnt targets, while TCF1 and TCF4 (also termed TCF7 and TCF7L2, respectively) display either activity depending on the context . Partially supporting this, TCF3 and TCF4 bind to TLEs with higher affinity than LEF1 or TCF1 .…”
Section: Is Tcf3 a Dedicated Repressor In The Transcriptional Switch?mentioning
confidence: 95%
“…The Wnt pathway facilitates short‐range signaling during development and in adult tissues. It has important roles in stem cell homeostasis and in the etiology of several cancers and human diseases . Transcriptional regulation by the Wnt pathway begins with the stabilization and nuclear accumulation of β‐catenin .…”
Section: Introductionmentioning
confidence: 99%
“…This signaling pathway is conserved throughout metazoans and is essential for cell proliferation, differentiation, development, self-renewal, and cell fate determination [29, 30]. Much evidence has suggested that the Wnt/β-catenin signaling pathway acts as a key regulator in PEMF-induced osteogenic differentiation of mesenchymal progenitor cells, bone formation and repair.…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%
“…In particular, developmental signaling pathways and abnormal reactivation of transcription factors in tumor cells are closely related to advanced and aggressive cancers [7, 8]. Limb-bud and heart (LBH) is an important transcription cofactor involved in embryonic development [9].…”
Section: Introductionmentioning
confidence: 99%